KOMUNIKASI PENYULUHAN PENYULUH LAPANGAN KELUARGA BERENCANA (PLKB) DALAM MEMBANGUN KAMPUNG KELUARGA BERENCANA (KB) DI DESA KEMANG INDAH KECAMATAN TAMBANG KABUPATEN KAMPAR - Murtia Arianis; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
KB villages are RW, vilages or equivalent regional units, which have certain criteria where there is integration of population, family planed, family development and related sector development programs that are carried out systematically and systematically. One of the villages designated to become a KB Village in Tambang District is Kemang Indah Village, which in the family data collection in 2015 is still a village with active family planning participants with a low Long-Term Contraception Method. With the establishment of the KB Village in Kemang Indah Village, it is expected that the number of active KB participants with MKJP will increase. The purpose of this study is to find out the extension communication planning process, the function of extension education and also to find out what obstacles occur in the counseling communication carried out by the PLKB in building KB villages in Kemang Indah Village.This studied used a qualitative research method with the subjects of the study consisting of 6 people who were selected by using purposive techniques that were determined based on the criteria and eksendendal techniques chosen based on the conditions at the time of observation. The technique of collecting data through interviews, observation and documentation. In analyzing data through the stages of data collection, data reduction, data presentation, and also drawing conclusions from the research results. And to achieve the validity of the data in this study the authors used data triangulation.The results of this study indicate that the PLKB only conducted six stages of counseling communication planning, namely collecting data through family data collection conducted in 2015, analyzing the data to find out that Kemang Indah Village was indeed included in the KB Village criteria, identifying problems which were the problem of low numbers KB participants with the MKJP method in Kemang Indah Village, formulated ways to achieve goals by planning to conduct individual methods as well as groups in delivering counseling messages about low MKJP numbers, conducting activities by conducting individual and group counseling, and for new evaluations and recommended. held after the upcoming 2020 family data collection. PLKB also carries out its function as a stimulus for the community to want to use MKJP, PLKB also conveys and adapts when conducting counseling, and PLKB also provides ongoing education and guidance by conducting counseling repeatedly to the community. The obstacles that occurred during the process of implementing counseling communication by the PLKB were only in the form of obstacles to adjusting the PLKB's time with the community when they wanted to do counseling.